CEPHEUS, a multi-project satellite for technology qualification. (December 2015) - Quero, José M.; León, Laura; Martínez, Daniel; Brey, Javier; Jiménez, Mar; Moreno, José M.; Rodríguez, Manuel; Nieto, Cristóbal; Castro, Pedro; Yagüe, Ignacio; Sánchez, Antonio; López, Demetrio; et al.
Abstract: An Andalusian company consortium is developing the CEPHEUS mission, whose purposes are the development of the first in-orbit validation inexpensive satellite. The objective of the project is to demonstrate the suitability of Cubesats as platforms for technology experimentation in space. Its launch is scheduled for the beginning of 2016. Highlights: The development of the first in-orbit validation low-cost satellite. The suitability of Cubesats for technology experimentation in space is demonstrated. The primary payload is a fuel cell to be characterized for space applications. The secondary payloads are Star Tracker, ADCS, transceiver and Sun Sensors on a Chip. The next objectives for future missions will be focused on a standardization process.